Turbulence in core-collapse supernovae. (9th April 2018) - Radice, David; Abdikamalov, Ernazar; Ott, Christian D; Mösta, Philipp; Couch, Sean M; Roberts, Luke F
Abstract: Multidimensional simulations show that non-radial, turbulent, fluid motion is a fundamental component of the core-collapse supernova explosion mechanism. Neutrino-driven convection, the standing accretion shock instability, and relic-perturbations from advanced nuclear burning stages can all impact the outcome of core collapse in a qualitative and quantitative way. Here, we review the current understanding of these phenomena and their role in the explosion of massive stars. We also discuss the role of protoneutron star convection and of magnetic fields in the context of the delayed neutrino mechanism.